posted by Juliet on .
Describe how the graph of y=f(-2x+6)+7 can be obtained from the graph of y=f(x). I am not understanding this transformation unit at all.
Since you do not say what the function
f(x) is, I cannot tell you the specific formula for y = f(-2x+6) +7.
Start with the graph of f(x). For each of a series of values of x, compute -2x +6, read off the corresponding y = f(-2x + 6); then add 7 to that. Replot as as f'(x) = f(-2x+6) +7. Then connect the dots. I suspect you will end up with a new curve that is translated (by the +6 and +7 terms), "squashed" (by the "2") and inverted (by the minus sign), compared to the original f(x) curve.